HUBUNGAN HIPONATREMIA, HIPOKALEMIA DANHIPOKLORINEMIA DENGAN PROGNOSIS PASIEN TRAUMATIC BRAIN INJURY DERAJAT SEDANG DAN BERAT - Deny Evander Pasamboan (2020)
Traumatic Brain Injury (TBI) is a pathological process in brain tissue due to external mechanical forces (trauma) that cause a decrease in consciousness. TBI patients generally excrete blood electrolyte levels, such as hyponatremia, hypokalemia and hypochlorinemia. The prognosis of TBI patients can worsen if taken with an abnormality that can restore balance and electrolytes in brain cells. The purpose of this study was to study the relationship between hyponatremia, hypokalemia and hypochlorinemia with the prognosis of TBI patients. This study uses a cross-sectional study design. Data were analyzed univariate and bivariate using Fisher's exact test (α = 0.05). The results of the study showed that in the EDD of the Cil Hyponatremia was found in 2 patients and hypochlorinemia in 3 patients. Bivariate statistical test results showed hyponatremia has a relationship with the prognosis of TBI patients (p = 0.04). Hypokalemia and hypochlorinemia have no relationship with the prognosis of TBI patients based on GCS scores in the ED (p = 0.67 and p = 0.1). The conclusion of this study is the comparison participation between hyponatremia with the prognosis of moderate and severe TBI patients